The Influence of Nahwu Knowledge on Arabic Text Reading Skills - Rahmad Khusen; Namiyah Fitriani; Lalu Rahmat Sugiara; Ibnu Imam Al Ayyubi; Yayang Lestari (Southeast Asian Journal of Islamic Education, 2025)
Understanding the Arabic language cannot be separated from mastery of foundational knowledge, such as Nahwu and Sharaf. Therefore, understanding Nahwu is very important for students so they can read Arabic texts fluently and avoid mistakes. The goal of learning maharah al-qira’ah is for students to read Arabic texts accurately and fluently. This study aims to analyze the influence of Nahwu knowledge on eighth-grade students’ ability to read Arabic texts at MTs Tarbiatul Islam Aziziah NW Wanasaba. The population of this study comprised eighth-grade students at MTs Tarbiatul Islam Aziziah NW Wanasaba, with a research sample of 45 eighth-grade students. The research method used was quantitative, with data collected through questionnaires and tests. The requirement tests for analysis include normality and linearity tests, while the data analysis technique uses the t-test. Based on the results of data analysis and hypothesis testing, a Sig. value of 0.000 (< 0.05) and a calculated t value of 4.645 (> t table 2.014) were obtained. This indicates that the alternative hypothesis (Ha) is accepted, meaning that Nahwu knowledge significantly influences reading skills in Arabic texts. The implications of this research underscore the need to integrate a more comprehensive, practical approach to teaching Arabic grammar into the curriculum to improve students’ reading skills significantly.